The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1029/98gl02015
|View full text |Cite
|
Sign up to set email alerts
|

Possible evidences of earthquake lightning accompanying the 1995 Kobe Earthquake inferred from the Nojima Fault Gouge

Abstract: Abstract. The Kobe earthquake of January 17, 1995, which had a weathered granite fault wall as shown by arrow B in Figure lb; magnitude of 7.2, was accompanied by earthquake hghtning and 3) the clayey fault gouge under the part where the charred (EQL). The fault gouge near ground level at the Nojima fault, roots were found was highly lithified and showed a lamellar near where the EQL was witnessed, was highly lithified and structure. anomalously mag-netized. The characterization of the fault gouge and the muds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 5 publications
0
37
1
Order By: Relevance
“…Recently, a number of examples of high magnetic susceptibility within fault gouges have been described from several faults related to large earthquakes (Enomoto and Zheng 1998;Nakamura and Nagahama 2001;Fukuchi et al 2005;Hirono et al 2006;Mishima et al 2006Mishima et al , 2009. Similarly, some core gouges with high magnetic susceptibility occur within the WFSD-1 core.…”
Section: Relationship Between Magnetic Susceptibility and Fault Rocksmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a number of examples of high magnetic susceptibility within fault gouges have been described from several faults related to large earthquakes (Enomoto and Zheng 1998;Nakamura and Nagahama 2001;Fukuchi et al 2005;Hirono et al 2006;Mishima et al 2006Mishima et al , 2009. Similarly, some core gouges with high magnetic susceptibility occur within the WFSD-1 core.…”
Section: Relationship Between Magnetic Susceptibility and Fault Rocksmentioning
confidence: 99%
“…Magnetic susceptibility and rock magnetism have commonly been used to understand the physical characteristics and chemical processes of fault slip zones (Enomoto and Zheng 1998;Nakamura and Nagahama 2001;Ferré et al 2005Ferré et al , 2012. Correlations have been reported between magnetic susceptibility anomalies in borehole log data and the presence of cataclastic zones and faults in the main drill borehole of the German Deep Drilling Project (KTB) (Bosum et al 1997), but the magnetic susceptibility of drill cuttings in the KTB do not support this correlation (Rauen et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Fukuchi (2003) indicated that Nojima fault gouge contains antiferromagnetic minerals such as kaolinite or smectite that can be changed into ferrimagnetic minerals such as maghemite by thermal dehydration. Nojima fault gouge contains siderite (FeCO 3 ) (Enomoto and Zheng 1998), which thermally decomposes into magnetite with carbon dioxide at 470 °C under reducing conditions (French 1971). Mishima et al (2009) showed that paramagnetic minerals such as siderite in Taiwan Chelungpu fault gouge changed into ferrimagnetic magnetite through thermal decomposition above about 400 °C.…”
Section: Introductionmentioning
confidence: 99%
“…First, ferrimagnetic minerals in the fault slip zone may acquire a thermal remanent magnetization (TRM) upon cooling (Piper and Poppleton 1988;Ferré et al 2014). Second, earthquake lightning may constitute an additional magnetization process (Enomoto and Zheng 1998;Ferré et al 2005). Third, a fault slip zone may acquire chemical remanent magnetization (CRM) due to neoformation of ferrimagnetic minerals by thermal decomposition during seismic slips (Nakamura et al 2002;Fukuchi 2003;Fukuchi et al 2005;Hirono et al 2006;Chou et al 2012); it can be explained that many kinds of antiferromagnetic or paramagnetic minerals are thermally decomposed into ferrimagnetic minerals.…”
Section: Introductionmentioning
confidence: 99%
“…But the melted zones do not constitute the continuos, non-interrupted barrier to charge spreading. Moreover, the most intense light flashes (lightning-like discharges) were seen above the strait with sea water having electric conductivity much higher than the typical conductivity of wet rocks (Enomoto and Zheng, 1998). So we propose alternative mechanism -the skin effect, invoking diffusion of electric currents and magnetic fields in the highly conductive medium from the current generation zone due to nonstationary magnetoelectrodynamic processes (Nemtchinov, 2002;Nemtchinov and Losseva, 2002;Losseva and Nemtchinov, 2002).…”
Section: Introductionmentioning
confidence: 99%